All Days 2011
DOI: 10.2118/140536-ms
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Shale Oil and Gas-Condensate Reservoir Production, Impact of Rock, Fluid, and Hydraulic Fractures

Abstract: Development of unconventional oil and gas reservoirs, particularly the shale gas, gas-condensate, and shale oil, has gained tremendous momentum in recent years. Energy companies aggressively are adding unconventional hydrocarbon resources to their portfolios. The unconventional resources usually refer to ultra low permeability reservoirs that cannot be produced at economic rates or volumes without stimulation of near well-bore regions. New technologies of horizontal well coupled with staged hydraulic fracturin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(62 citation statements)
references
References 6 publications
2
58
0
Order By: Relevance
“…Orangi et al (2011) for GOR=1000 oil e Solution gas-oil ratio d p b =∼3250 psi reported for a GOR=1000 scf/stb oil in Figure 2 in Orangi et al (2011) span the bottom-hole area of 10,500 acres.…”
Section: Resultsmentioning
confidence: 99%
“…Orangi et al (2011) for GOR=1000 oil e Solution gas-oil ratio d p b =∼3250 psi reported for a GOR=1000 scf/stb oil in Figure 2 in Orangi et al (2011) span the bottom-hole area of 10,500 acres.…”
Section: Resultsmentioning
confidence: 99%
“…The oil production is about double in ten years when the rock compressibility is 25 times higher as shown in Figure 6(b). These trends were also observed by Orangi et al (2011). Lower compressibility rocks do not permit the structure to deform; on the other hand, higher compressible rock sustains the pressure of reservoir by squeezing the rock and reducing the pore space for overburden pressure when the pressure in the pore is reduced in course of production.…”
Section: Effect Of Rock Compressibilitymentioning
confidence: 65%
“…Fracture spacing affects the performance of gas-oil gravity drainage largely when the ratio of fracture spacing and fracture height is larger than 0.3 (Clemens and Wit, 2001). Oil production increases with increase in fracture permeability up to 10,000 mD and with increase in the fracture -matrix surface contact area (Orangi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Gas and oil components were sourced from available mudlogs and missing data points were filled in with synthetic Eagle Ford black oil properties (Orangi et al, 2011) matching with the provided oil gravity (41 °API) and gasoil ratio (1,000 scf/stb) data. The Peng-Robinson Equation of State was used to predict the phase equilibrium compositions of the oil and gas phases as defined by:…”
Section: Multiphase Componentsmentioning
confidence: 99%